2012
DOI: 10.1002/pd.3841
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of congenital diaphragmatic hernia: a 12‐year experience

Abstract: Abnormal karyotype was more common when CDH was associated with other anomalies. In multivariate analysis, lower birthweight and prenatal diagnosis had a significant impact on survival. Only prenatally diagnosed CDH survival figures should be utilised in prenatal counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
5
19
0
7
Order By: Relevance
“…For pregnancies with an antenatal diagnosis of CDH, 62.8% resulted in a live birth, with 73% of these surviving to surgery and a 91% postsurgery survival in the absence of prenatal fetal therapy such as fetoscopic tracheal occlusion (FETO). This is akin to the results from population‐based studies on CDH in the United Kingdom and France . In Western Australia, terminations of pregnancy are permitted on request or when the life, physical, or mental health of the woman is endangered, up to 20 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
“…For pregnancies with an antenatal diagnosis of CDH, 62.8% resulted in a live birth, with 73% of these surviving to surgery and a 91% postsurgery survival in the absence of prenatal fetal therapy such as fetoscopic tracheal occlusion (FETO). This is akin to the results from population‐based studies on CDH in the United Kingdom and France . In Western Australia, terminations of pregnancy are permitted on request or when the life, physical, or mental health of the woman is endangered, up to 20 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%
“…An additional 3.5–13% of cases without identifiable karyotype abnormalities have copy number variants (CNVs) including microdeletions or microduplications identifiable by chromosome microarray analysis, which offers higher resolution over a standard karyotype [1220]. Aneuploidies and CNVs are associated with increased neonatal mortality [12,18].…”
Section: Geneticsmentioning
confidence: 99%
“…This chance is similar to that described by Taheri and Kadir 4 for a fetus to be affected by both conditions. Samangaya et al 6 reported that the risk of having a chromosomal abnormality in a case of congenital diaphragmatic hernia after being diagnosed through ultrasound is up to 15.9%, which enhances the importance of fetal karyotyping in this situation. 7 The chromosomal abnormalities observed among patients with congenital diaphragmatic hernia include tetrasomy 12p mosaicism and trisomy 18.…”
Section: Discussionmentioning
confidence: 99%
“…7 The prognosis for diaphragmatic hernia is still very poor. 6 Fetuses with Klinefelter syndrome usually do not present associated major malformations and, differently from other chromosomal anomalies, such as Turner syndrome or trisomy 13 and 18, do not show increased rates of intrauterine mortality. 2,9 Although the risk of dying due to a variety of diseases, such as malignant neoplasms, diabetes type 2 and respiratory and circulatory system diseases may be greater among Klinefelter patients, 10 we believe that the chromosomal anomaly present in our patient did not interfere with the prognosis associated with his diaphragmatic hernia.…”
Section: Discussionmentioning
confidence: 99%